Pengaruh Media Digital dan Kompetensi Digital terhadap Ekspansi Usaha Kuliner UMKM - Juli Meliza; Vidya Fathimah; Hafizah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to provide empirical evidence on the importance of digital competency development and digital media utilization as strategic efforts to enhance business expansion in the digital era, focusing on the Makcik Cam culinary MSMEs. Makcik Cam operates in the production and sale of traditional Malay cakes and local market snacks in Medan, North Sumatra. The study was conducted from January to March 2025. The population includes all micro and small culinary business actors within the Makcik.cam network, both as primary producers and affiliated resellers or outlets coordinated under the Makcik Cam MSMEs. A simple random sampling technique was used. Multiple regression analysis revealed that digital media utilization has a significant effect on business expansion (t = 9.040, Sig. = 0.000). However, digital competency showed no significant partial effect (t = 0.805, Sig. = 0.425). Nonetheless, jointly, both variables significantly influence business expansion. The findings highlight the critical role of digital transformation, online marketing strategies, and digital skills training to improve business readiness and operational efficiency.